Determination of Phytochemicals, Minerals, and Evaluation of Antioxidant, Antidiabetic Activities of Young Fronds of Diplazium esculentum: A Vegetable of Tripura, India - Manna, K.; Debnath, B.; A. Ikbal, A. M.; Paul, K.; Rajkhowa, A.; Majumder, R. (Journal of Scientific Research, 2023)
Diplazium esculentum belongs to the family Athyriaceae, an edible fern rich in micronutrients, beta-carotene, folic acid, and minerals like calcium, iron, and phosphorus. The present study aims to determine secondary metabolites and minerals content and evaluate the antioxidant and antidiabetic activities of young fronds of Diplazium esculentum. The plant extract was prepared by the Soxhlet apparatus method. Total alkaloids and total tannin content were determined by the titrimetric method. Folin and Ciocalteu's colorimetric method used gallic acid as a standard drug to determine total phenols. The antioxidant activity of plant extract was evaluated by DPPH free radical scavenging and hydrogen peroxide scavenging assay. α-amylase inhibition assay was performed for evaluation of the antidiabetic activity of plant extract. Fronds of Diplazium esculentum contain a significant number of total alkaloids (145.54±1.49), phenols (174.2±0.95), and tannins (263.96±1.32) mg/g of dry extract. Fronds of Diplazium esculentum also contain a significant amount of minerals. Diplazium esculentum shows significant antioxidant activity compared to the standard drug ascorbic acid and antidiabetic activity compared to the standard drug metformin. Based on these findings, young fronds of Diplazium esculentum can be recommended as a good source of phytochemicals and minerals. It also shows significant antioxidant and antidiabetic activities.